Abbreviated Antiplatelet Therapy After Coronary Stenting in Patients With Myocardial Infarction at High Bleeding Risk - Smits, Pieter C; Frigoli, Enrico; Vranckx, Pascal; Ozaki, Yukio; Morice, Marie-Claude; Chevalier, Bernard; Onuma, Yoshinobu; Windecker, Stephan; Tonino, Pim A L; Roffi, Marco; Lesiak, Maciej; Mahfoud, Felix; et al. (Journal of the American College of Cardiology, 2022)
BACKGROUND: The optimal duration of antiplatelet therapy (APT) after coronary stenting in patients at high bleeding risk (HBR) presenting with an acute coronary syndrome remains unclear. OBJECTIVES: The objective of this study was to investigate the safety and efficacy of an abbreviated APT regimen after coronary stenting in an HBR population presenting with acute or recent myocardial infarction. METHODS: In the MASTER DAPT trial, 4,579 patients at HBR were randomized after 1 month of dual APT (DAPT) to abbreviated (DAPT stopped and 11 months single APT or 5 months in patients with oral anticoagulants) or nonabbreviated APT (DAPT for minimum 3 months) strategies. Randomization was stratified by acute or recent myocardial infarction at index procedure. Coprimary outcomes at 335 days after randomization were net adverse clinical outcomes events (NACE); major adverse cardiac and cerebral events (MACCE); and type 2, 3, or 5 Bleeding Academic Research Consortium bleeding. RESULTS: NACE and MACCE did not differ with abbreviated vs nonabbreviated APT regimens in patients with an acute or recent myocardial infarction (n = 1,780; HR: 0.83; 95% CI: 0.61-1.12 and HR: 0.86; 95% CI: 0.62-1.19, respectively) or without an acute or recent myocardial infarction (n = 2,799; HR: 1.03; 95% CI: 0.77-1.38 and HR: 1.13; 95% CI: 0.80-1.59; Pinteraction = 0.31 and 0.25, respectively). Bleeding Academic Research Consortium 2, 3, or 5 bleeding was significantly reduced in patients with or without an acute or recent myocardial infarction (HR: 0.65; 95% CI: 0.46-0.91 and HR: 0.71; 95% CI: 0.54-0.92; Pinteraction = 0.72) with abbreviated APT. CONCLUSIONS: A 1-month DAPT strategy in patients with HBR presenting with an acute or recent myocardial infarction results in similar NACE and MACCE rates and reduces bleedings compared with a nonabbreviated DAPT strategy. (Management of High Bleeding Risk Patients Post Bioresorbable Polymer Coated Stent Implantation With an Abbreviated Versus Prolonged DAPT Regimen [MASTER DAPT]; NCT03023020).
Keywords: antikoagulancia; dimaprit; dual antiplatelet therapy; výsledek terapie; Anticoagulants; krvácení; Polymers; lidé; koronární angioplastika; antiplatelet therapy; Platelet Aggregation Inhibitors; Treatment Outcome; Percutaneous Coronary Intervention; Stents; Hemorrhage; kombinovaná farmakoterapie; polymery; Myocardial Infarction; inhibitory agregace trombocytů; acute coronary syndrome; Dimaprit; percutaneous coronary intervention; stenty; infarkt myokardu; Drug Therapy, Combination; Humans